Potassium:calcium balance, relationship with vapor pressure deficit and photosynthetically active radiation in greenhouse tomato - Salas-Rivera, Ramiro; Valdez-Aguilar, Luis Alonso; Alvarado-Camarillo, Daniela; Rascón-Alvarado, Emilio; Peña-Ramos, Fidel Maximiano; González-Fuentes, José Antonio (REVISTA TERRA LATINOAMERICANA, 2020)
Greenhouse tomato production requires technical knowledge such as the management of the nutrient solution and its interaction with environmental conditions. Imbalances between nutrients such as potassium (K) and calcium (Ca) can occur in the nutrient solution; Moreover, the flow of sap and nutrients translocation are affected by the vapor pressure deficit (VPD) and photosynthetically active radiation (PAR). The present study was carried out with the objective to determine the optimal balance of K and Ca depending on VPD and PAR prevailing during the development of the fruits of 10 clusters in tomato; the first five clusters were developed during the spring, while the clusters sixth to tenth during the summer. Plants were irrigated with solutions whose K:Ca balance was: 0.54, 0.64, 0.78, and 0.82. The balance did not affect fruit quality in spring, although in summer, balances 0.64 and 0.78 reduced soluble solids. In spring, fruit yield in each of the five clusters was influenced by the K:Ca balance as well as by the VPD; the clusters had a higher fruit production when the K:Ca balance was 0.64 and the VPD was 2.81 KPa. During the summer, the highest yield in fruits was in plants treated with a balance of 0.54 and the VPD was 2.50 or 2.74 KPa. The K:Ca balance during the spring correlated negatively with the VPD, however, in the summer, the correlation was positive. In spring, the K:Ca optimum balance should be 0.78-0.82 when PAR reached a maximum of 102‑142 μmol m-2 s-1, while extreme PAR levels should be accompanied by a reduction in the K:Ca balance.